Successful Fibrinolytic Treatment in a Pregnant Woman with Acute Mitral Prosthetic Valve Thrombosis - BarışKaya, Ergün (Clin Cardiol, 2010)
Pregnant patients with mechanical prosthetic heart valves pose a great problem for medical management. The problem is even greater in a pregnant woman with mechanical valve thrombosis. This article describes a pregnant woman with prosthetic mitral valve thrombosis who had a successful fibrinolytic treatment. Copyright © 2010 Wiley Periodicals, Inc.